Seroprevalence of dirofilariasis in dogs in Sukabumi Regency - Ridwan, Yusuf; Sudarnika, Etih; Ilyas, Abdul Zahid (ARSHI Veterinary Letters, 2023)
Dirofilariasis is a serious zoonotic disease in dogs. This study aimed to measure the prevalence and determine the risk factors of dirofilariasis in the Sukabumi Regency. A total of 152 blood samples were collected from dogs in two sub-districts in Sukabumi which have different topographic characteristics, namely Jampang Tengan District which is a hilly area, and Cisolok District which is a coastal area. Blood serum was examined using the commercial rapid test kit CHW Ag Test Kit 2.0 ® Bionote to detect the presence of the Dirofilaria immitis adult worm antigen. The results showed that the seroprevalence of dirofilariasis in dogs in the Sukabumi Regency was 20.4%. Areas with hilly characteristics have a higher prevalence of dirofilariasis than coastal areas do. The incidence of dirofilariasis in the Sukabumi Regency was not influenced by sex, method of keeping, or age of the dog.